PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN MENGAMBIL PRODUK DEPOSITO DI BRI SYARIAH KCP TANJUNGSARI - Lusyyani, Nurbaethi Nanda; Rapida, Ida (STIBANKS Al Ma'soem Bandung, 2018)
This research is conducted to know how big influence of promotion mix to decision to take deposit product at BRI Syariah KCP Tanjungsari. The method used in this research is quantitative descriptive method. Primary data was obtained through questionnaires distributed to 30 respondents. Data is processed with the help of IBM SPSS Statistic 23.The results showed that the promotion mix influenced the decision of depositors by 0.345 and was in the low category. Results from the calculation of Test Z is known that Z arithmetic> Z table or 1.828> 1.64. This means H0 is rejected and H1 accepted. This means that there is influence of promotion mix to decision depositors at BRI Syariah KCP Tanjungsari. The value of determination coefficient obtained by 0.119 or 11.9%, it means that in general the promotion mix contributes 11.9% to the decision of depositors. While the rest of 88.1% influenced by other factors. Other factors can be from price, location, service quality and so on.This research reveals that depositors expect that BRI Syariah can promote more and more attractive deposit products such as in advertisements conducted on TV and radio that are often seen and heard by the public. Later in the voucher and souvenir gift can be given fairly to each depositors regardless of the amount of funds saved although in the form of different rewards as well as further research on other factors that further influence the decisions of depositors such as price, location, service quality and etc.